Call for Reviewers - Saleh, Amany (Journal of Interdisciplinary Studies in Education, 2013)
We are delighted to present the first issue of a new and exciting journal in the field of education, Journal of Interdisciplinary Studies in education. The journal os peer-reviewed and will be available online and in print. The journal publishes two issues a year.